1 2 2

:

  1. #1

    Jul 2012
    5,302

    :-

    :-
    1- /3 = 5 /6
    :-

    6 = 3 5
    6 = 15 ........... = 15 /6
    = 2.5

    2- /3 = 12 /
    :-

    = 3 12
    ^2 = 36
    = ( 36 ) ............. = 6

    3- 1 / 2 + 3 = 2 / 3 - 4 .... - 3/ 2 , 4 /3

    :-

    1 ( 3 - 4 ) = 2 ( 3 + 3 )
    3 - 4 = 6 + 6
    3 - 4 = 6 + 4
    - = 10 ................. = - 10


    :-
    14 / + 4 - 5 / + 2 = 1
    - 2 , - 4
    :-

    14 ( + 2 ) / ( +4 ) ( + 2 ) - 5 ( + 4 ) / ( + 4 ) ( + 2 ) = 1
    14 + 28 - 5 - 20 = ( + 4 ) ( + 2 )
    = 9 + 8 = ^2 + 6 + 8
    ^2 - 3 = 0
    ( - 3 ) = 0
    = 0 - 3 = 0 ............. = 3


    :-

    1/ ^2 + + 1 = - 1 / 7
    :-
    =
    1/ ^2 + + 1 = - 1 / 7
    = ( - 1 ) ( ^2 + + 1 ) = 1 7
    = ^3 + ^2 + - ^2 - - 1 = 7
    = ^3 - 1 = 7
    ^3 = 7 + 1 .......... ^3 = 8
    = + 2 , - 2


    :-

    - 2 / 3 - - 3 / 4 = 1 / 2
    :-
    3 , 4 , 2
    12
    12

    4 ( - 2 ) - 3 ( - 3 ) = 6
    4 - 8 - 3 + 9 = 6
    + 1 = 6
    = 6 - 1 = 5
    = 5


    :-

    2 + 1 / 3 + 1 = 8 - / 4 + 3
    :-
    ( 2 + 1 ) (4 + 3 ) = ( 3 + 1 ) ( 8 - )
    8 ^2 + 6 + 4 + 3 = 24 - 3 ^2 - + 8
    8 ^2 + 3 ^2 + 6 + 4 - 24 + = 8 - 3
    11 ^2 -13 = 5
    11 ^2 - 13 - 5 = 0


    :-

    + 5 / 6 - ( - 3 ) ( + 5 ) / 4 = 4 / 3
    :-
    24
    4 ( + 5 ) - 6 ( - 3 ) ( + 5 ) = 8 4
    4 + 20 -6 ( ^2 + 5 - 3 - 15 ) = 32
    4 + 20 - 6 ^2 - 30 + 18 + 90 = 32
    - 6 ^2 - 8 + 110 = 32
    - 1
    6 ^2 + 8 - 110 = - 32
    6 ^2 + 8 - 110 + 32 = 0
    6 ^2 + 8 - 78 = 0
    ( 2 + 6 ) ( 3 - 13 ) = 0

    = - 3

    = 13 / 3


















  2. #2
      Eiman
    Jul 2011
    -
    14,750

    :

    .......

: 1 (0 1 )